RNA atlas and competing endogenous RNA regulation in tissue-derived exosomes from luminal B and triple-negative breast cancer patients - Wang, Ji; Zhang, Xianyu; You, Zilong; Meng, Yuhuan; Fan, Xijie; Qiao, Guangdong; Pang, Da (Frontiers in Oncology, 2023)
Background Luminal B and triple-negative breast cancer (TNBC) are malignant subtypes of breast cancer (BC), which can be attributed to the multifaceted roles of tissue-derived exosomes (T-exos). Competing endogenous RNA (ceRNA) networks can regulate gene expression post-transcriptionally. Methods RNAs in T-exos from luminal B BC (n=8) and TNBC (n=8) patients were compared with those from persons with benign breast disease (n=8). The differentially expressed (DE) mRNA, microRNA (miRNA), and long noncoding RNA (lncRNA) target genes were annotated using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) to reveal the relevant biological processes.The ceRNA networks were constructed to show distinct regulation, and the mRNAs involved were annotated. The miRNAs involved in the ceRNA networks were screened with the Kaplan–Meier Plotter database to identify dysregulated ceRNAs with prognostic power. Results In total, 802 DE mRNAs, 441 DE lncRNAs, and 104 DE miRNAs were identified in luminal B BC T-exos, while 1699 DE mRNAs, 590 DE lncRNAs, and 277 DE miRNAs were identified in TNBC T-exos. Gene annotation revealed that the RAS–MAPK pathway was the primary biological process in luminal B BC T-exos, while endocrine system development and growth were the main processes in TNBC T-exos. Survival analysis established seven survival-related lncRNA/miRNA/mRNA regulations in luminal B BC T-exos, and nineteen survival-related lncRNA/miRNA/mRNA regulations in TNBC T-exos. Conclusion In addition to survival-related ceRNA regulations, ceRNA regulation of RAS–MAPK in luminal B and endocrine system development and growth regulation in TNBC might contribute to the tumorigenesis of BC.